Women’s Communication Attitude in Pepadun Traditional Marriage in Digital Era - Gustina Zainal, Anna; Saleh, Amiruddin; S Hubeis, Aida Vitayala; Matindas, Krisharini Matindas (Opción, 2019)
This research aims to investigate how women’s communication attitude is in Pe- padun traditional marriage. This research is designed as quantitative approach, strengthen by qualitative approach. The samples are 126 people. The location of the research is in the Regency of North Lampung. The result of the research found that men were rarely passive to get information re- garding Pepadun traditional marriage. So did women. They rarely showed passive attitude towards information about the Pepadun traditional marriage. The aware- ness to preserve and to be actively involved in the traditional marriage made wom- en actively gather information regarding the marriage. Women tended to interact and discuss to get the information from any sources and the process of gathering information could be from any places. Generally, women’s communication is more personal than men’s communication. Men often decide without negotiating it with their wives, except from matters re- lated to economic issue. In return, women never decide matters regarding the marriage without discussing with their husbands. Women’s attitude in sending information regarding the Pepadun traditional marriage whether it is directly or through media is still done with high accuracy and good actualization.